Pengaruh Pupuk Sampah Kota Dan Pupuk Kandang Sapi Terhadap Pertumbuhan Vegetatif Dan Hasil Panen Pakcoy (Brassica Rapa) Pada Aluvial Di Kabupaten Indramayu - Yulina, Henly; Ambarsari, Wiwik (Universitas Wiralodra, 2022)
The objective of this research was to find out the effect of municipal solid waste compost and cow manure on plant height, leaf length, and harvest weight of pakcoy (Brasica rapa) in Andisols in Indramayu Regency. This study used a randomized block design factorial with two factors. The first factor is municipal waste compost and the second factor is cow manure. Each of them consisted of 4 levels : 0%, 3.0%, 6.0%, and 9.0% with two replication. The results showed that there was an interaction between municipal solid waste compost and cow manure on the plant heights of pakcoy 14, 21, and 28 HST, but there was no interaction at 7 HST. The statistical results show that the combination of municipal solid waste compost with cow manure has an effect on the height of pakcoy 14, 21, and 28 HST, but the height of pakcoy 7 HST is influenced by the independent influence of cow manure. There was an interaction between municipal solid waste compost and cow manure on the leaf length of pakcoy 7, 14, 21, and 28 HST, and there was an interaction between municipal waste compost and cow manure on the harvest weight of pakcoy. The application of organic matter, both municipal solid waste compost and cow manure to the soil can increase plant height, leaf length, and harvest weight of pakcoy.